Can International Local Government Partnerships Make a Difference? Lessons from the Australia – Papua New Guinea Good Practice Scheme (Commonwealth Journal of Local Governance, 2009)
This article explores the contribution that local government to local government partnerships can make in bringing about more effective and sustained decentralisation through developing the capacity of local governments to deliver improved services to the communities they serve. After almost 15 years of decentralization many of Papua New Guinea’s local governments struggle to maintain essential functions. Building on existing relationships, the Commonwealth Local Government Good Practice Scheme seeks to utilize the resources and knowledge of Australian local councils in partnership with those in Papua New Guinea to build capacity and improve the management and delivery of services to communities. This article examines the program to date, outlining both the successes and failures, but also the potential role such partnerships can play in the deepening of democratic governance at the local level.